Impact of COVID‐19 on emergency medicine resident procedure performance. Issue 6 (20th December 2022) - Bruno, Tony W.; Janwadkar, Rohan; Clayton, Lisa M.; Hughes, Patrick G.; Solano, Joshua J.; Shih, Richard D.; Bilello, Leslie A.; Hughes, Mary J.; Alter, Scott M.
Abstract: Background: As a result of the COVID‐19 pandemic, patterns of patient presentations and medical education have changed, potentially resulting in fewer and different types of patient encounters. Procedural proficiency is a cornerstone of emergency medicine (EM) training, and residents must meet Accreditation Council for Graduate Medical Education (ACGME) requirements to graduate. It is feared there may have been a pandemic‐induced decrease in opportunities for residents to perform procedures. This study investigates the change in procedures performed by EM residents during the initial year of the pandemic. Methods: This study utilized a multicenter retrospective design. Across three EM residency programs, logs of 14 ACGME‐required procedures performed by residents were reviewed. For each procedure, counts were compared prepandemic year (March 2019 to February 2020) to during pandemic year (March 2020 to February 2021). Procedures were further grouped into 4‐month periods: March to June, July to October, and November to February. Results: A total of 113 EM resident physicians were included in this study. Procedures performed by EM residents tended to decrease during the COVID‐19 pandemic. There were statistically significant decreases in number of annual cricothyrotomies (2.4 vs. 0.9, p < 0.001) and pediatric trauma resuscitations (5.7 vs. 3.9, p = 0.024). Comparing the first 4‐month periods of each year, there were significant decreases in cardiac pacing (6.3 vs. 5.4, p = 0.038), chest tubes (2.2 vs. 1.0, p < 0.001), cricothyrotomies (0.6 vs. 0.1, p = 0.001), intubations (8.2 vs. 4.4, p = 0.002), and pericardiocenteses (1.7 vs. 0.2, p < 0.001). Conclusions: The COVID‐19 pandemic has led to a decrease in the number of procedures performed per EM resident in many of the domains required by the ACGME. Although only some procedures had statically significant decreases, it remains to be seen if this will lead to decreased resident procedural competency. Further research may be required in this area to determine any such effect.